The Influence of Employee Engagement, Social Environment, and Motivation on Performance at PT Telkom Indonesia - Subekti, Toni Ahmad; Mulya, Fitra; Akmal, Junivar; Sari, Nurmala; Meilita, Willi (Journal of Business Management and Economic Development, 2025)
This research aims to determine the influence of Employee engagement (X1), Social Environment (X2), and Motivation (X3) on Employee Performance (Y). The total number of respondents was 53 respondents. The analysis used in this research is multiple linear regression. The results show that employee engagement positively and significantly affects employee performance, with a regression coefficient of 1.362. In contrast, motivation has a regression coefficient of 0.453 and a positive and significant effect. However, the Social Environment has a negative effect on employee performance, with a regression coefficient of -0.200. In addition, the interaction between employee engagement and motivation showed a more significant effect, indicating that combining these factors effectively improves performance. The study also found that social environment had a negative influence. Among the three independent variables consisting of employee engagement (X1), social environment (X2), and motivation (X3), the dominant influence on employee performance (Y) is Motivation (X2) because the highest t-count value is 1,362. Another result is that employee engagement (X1), social environment (X2), and motivation (X3) can explain the employee performance variable (Y) by 43.7%, while the rest explains other variables not examined in this research by 56.3%. The implication of this study is the importance of integrating comprehensive programs to improve employee engagement and work motivation enhancement strategies to improve overall employee performance.